PATIENTS EMERGENCY CALLING WITH TRAUMATIC DENTAL INJURIES IN PERMANENT TEETH - Mihaela Tănase; Aneta Munteanu; Ioana Stanciu; Daciana Zmarandache; Cătălina Farcaşiu; George Ion (Amaltea Medical Publishing House, 2018)
The aim of the study was to assess the prevalence and distribution of traumatic dental injuries (TDI) in permanent teeth (PT) in a sample of patients who sought treatment at a pedodontic clinic. Material and method. A retrospective descriptive study on 452 patients (212 boys) aged 8 to 16 years, who seek an emergency at the Pedodontics Department, Carol Davila University during one year. Prevalence of TDI and distribution according to age, gender, the environment origin, mean number of affected teeth/patient, topography, type of injury and time elapsed until dental care was provided. Data were analyzed using Microsoft Excel 2010 şi SPSS 20.0 (for Windows). Results. Prevalence of TDI was 9.7%. Girls were more affected than boys (55% versus 45% (NS, p>0.05). Children aged 8 were the most affected. The most patients had two involved teeth (37%), with a mean number of affected teeth/child=1.72. About 2/3 of affected teeth were upper central incisors, followed by upper lateral incisors (16%), teeth from the right side being more prevalent. Type of injuries: fractures (64%), luxations (27%) and mixed (9%). Time elapsed between injury and treatment was more than 48 hours for 47% of patients and 18% of patients needed prescriptions or anti-tetanus vaccines. Conclusions. TDI in PT is a public health problem. It is necessary to inform the people involved (parents, teachers, coaches, pediatricians) regarding the early attending to the pedodont of patients with TDI in order to avoid complications.